The Chinese language [videorecording] (Falls Church, VA : Landmark Media, 2001)
This episode examines the seven " dialects" of the Chinese language-all spoken diferntly from one another but sharing the same writing system. Chinese differs from other languages intehat is is all single-syllbles with multiple meanings depending on pronunciation. This episode follows the evolution of the Chinese dialects, which originated 2,800 years ago in the Sino-Tibetan family of East Asian languages. mandarin was adopted as the official language of the Chinese empire inn 700 A.D. but ws replaced by Baihua writing in 1917. The simpler modern Mandarin known as Putonghua was adopted in 1956.